ART adherence and viral suppression are high among most non-pregnant individuals with early-stage, asymptomatic HIV infection: an observational study from Uganda and South Africa - Haberer, Jessica E; Bwana, Bosco M; Orrell, Catherine; Asiimwe, Stephen; Amanyire, Gideon; Musinguzi, Nicholas; Siedner, Mark J; Matthews, Lynn T; Tsai, Alexander C; Katz, Ingrid T; Bell, Kathleen; Kembabazi, Annet; et al. (Journal of the International AIDS Society, 2019)
Introduction: The success of universal antiretroviral therapy (ART) access and aspirations for an AIDS-free generation depend on high adherence in individuals initiating ART during early-stage HIV infection; however, adherence may be difficult in the absence of illness and associated support. Methods: From March 2015 to October 2017, we prospectively observed three groups initiating ART in routine care in Uganda and South Africa: men and non-pregnant women with early-stage HIV infection (CD4 > 350 cells/lL), pregnant women with early-stage HIV infection and men and non-pregnant women with late-stage HIV infection (CD4 < 200 cells/lL). Socio-behavioural questionnaires were administered and viral loads were performed at 0, 6 and 12 months. Adherence was monitored electronically. Results: Adherence data were available for 869 participants: 322 (37%) early/non-pregnant, 199 (23%) early/pregnant and 348 (40%) late/non-pregnant participants. In Uganda, median adherence was 89% (interquartile range 74 to 96) and viral suppression was 90% at 12 months; neither differed among groups (p > 0.72). In South Africa, median adherence was higher in early/non-pregnant versus early/pregnant or late/non-pregnant participants (76%, 37%, 52%; p < 0.001), with similar trends in viral suppression (86%, 51%, 79%; p < 0.001). Among early/non-pregnant individuals in Uganda, adherence was higher with increasing age and lower with structural barriers; whereas in South Africa, adherence was higher with regular income, higher perceived stigma and use of other medications, but lower with maladaptive coping and cigarette smoking. Discussion: ART adherence among non-pregnant individuals with early-stage infection is as high or higher than with late-stage initiation, supporting universal access to ART. Challenges remain for some pregnant women and individuals with late-stage infection in South Africa and highlight the need for differentiated care delivery.
Keywords: HIV; Antiretroviral therapy; Adherence; Stage of disease; Sub-Saharan Africa